Framing the Golgotha in Renaissance Painting - Péter Bokody (Sillages Critiques)
The coming together of frames and spaces poses a particular challenge at the dawn of early modern painting. In the master narrative of the period the emphasis is customarily put on the emergence of three-dimensional space. Initially painters aimed at generating homogenous depth within their work, a prerequisite of coherent immersive experience. However, hybridization of perspectivic registers was also explored. The importance of frames cannot be overlooked in this context. They either separate the various incompatible space-segments within the work, or by the virtue of their own fictiveness, they introduce the heterogenous element itself. In this essay, I explore some works that complicate further this dynamic link between frame and space. I will first turn to an example where the frame does not regulate the insertion of an independent register: the Ambassadors by Hans Holbein the Younger. In order to contextualize the radicality of this solution, I will examine a series works by Pietro Lorenzetti, Fra Angelico, Benozzo Gozzoli, Neri di Bicci, Sandro Botticelli and Fra Bartolommeo, in which embedded votive images are placed on or around the frame of the work. They are not mere objects; they carry elements of an independent virtual space which are at odds both with the frame and the principal perspective of the painting. They explore the same motif, that of a little panel for private devotion depicting the Golgotha, superimposed upon a larger painting. The distorted skull and the crucifix on Holbein’s painting map to this iconography and offer its personalized rereading.